Pupils handicapped by speech disorders : a report of the advisory council on education in Scotland. - Scottish Education Department (Edinburgh : His Majesty's Stationery Office, 1951)
Hoe is het gesteld met de opvang van leerlingen in het Schotse onderwijs die spraakproblemen hebben?